Instant in situ formation of a polymer film at the water–oil interface. Issue 48 (1st November 2022) - Coppola, Sara; Miccio, Lisa; Wang, Zhe; Nasti, Giuseppe; Ferraro, Vincenzo; Maffettone, Pier Luca; Vespini, Veronica; Castaldo, Rachele; Gentile, Gennaro; Ferraro, Pietro
Abstract : A completely new method for easy and quick formation of a thin polymer film at the special setting of a stratified oil/water interface. Morphological SEM and quantitative full-field characterization have been reported using digital holography. Abstract : The water–oil interface is an environment that is often found in many contexts of the natural sciences and technological arenas. This interface has always been considered a special environment as it is rich in different phenomena, thus stimulating numerous studies aimed at understanding the abundance of physico-chemical problems that occur there. The intense research activity and the intriguing results that emerged from these investigations have inspired scientists to consider the water–oil interface even as a suitable setting for bottom-up nanofabrication processes, such as molecular self-assembly, or fabrication of nanofilms or nano-devices. On the other hand, biphasic liquid separation is a key enabling technology in many applications, including water treatment for environmental problems. Here we show for the first time an instant nanofabrication strategy of a thin film of biopolymer at the water–oil interface. The polymer film is fabricated in situ, simply by injecting a drop of polymer solution at the interface. Furthermore, we demonstrate that with an appropriate multiple drop delivery it is also possible to quickly produce a large area film (up to 150 cm 2 ). The film inherently separates the two liquids, thus forming a separation layer between them and remains stable at the interface for a long time. Furthermore, we demonstrate the fabrication with different oils, thus suggesting potential exploitation in different fields ( e.g. food, pollution, biotechnology). We believe that the new strategy fabrication could inspire different uses and promote applications among the many scenarios already explored or to be studied in the future at this special interface environment.